The Effect of Parental Support on the Learning Motivation of Grade IV Elementary School Cluster 3 Students of Kempo District for the 2022/2023 Academic Year - Ardiansyah Ardiansyah; Hari Witono; Abdul Kadir Jaelani (International Journal of Social Service and Research, 2023)
Based on the results of initial observations made in grade IV of SDN Cluster 3 Kempo District on March 3, 2020, that work and high economic demands in this modern era make parents work hard to meet their daily family needs, so that the time spent on children is very limited to pay attention and monitor children's learning activities, So that children learn at will and in their daily lives are used to play PlayStation, games commuted on computers and the internet. Parental support given to children is still not optimal. Parental support is very important because it can motivate them to achieve achievements and can build self-confidence and foster enthusiasm when children face problems